PERAN UNDANG-UNDANG NOMOR 24 TAHUN 2009 TERHADAP PENDIDIKAN BAHASA INDONESIA - Jatut Yoga Prameswari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2017)
Abstract: Law No. 24 of 2009 Article 25 of the State Language. This article incorrectly stated that the Indonesian only serves as the official language of the state, introduction of education. Act real manifestation of our government's concern about language education in Indonesia in particular. Where language is an everyday communication tool to get attention of the entire community languages. With the existence of these laws to strengthen the Indonesian legal position in pengguanaanya. Indonesian education is one extension of the role of the law as the cultivation and development of Indonesian in particular. Keywords: Education, Indonesian Education, Law No. 24 Year 2009